Pengaruh Leverage dan Ukuran Perusahaan Terhadap Kebijakan Dividen Pada Perusahaan Indeks High Dividend 20 - Rina Saputeri; Muhammad Iqbal Pribadi; Sri Wahyuni Jamal (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This This study aims to determine the effect of leverage and company size on dividend policy. The method used in this study is panel data regression, and purposive sampling was used in data collection. The main population in this study consists of companies listed on the High Dividend 20 Index, totaling 38 companies, with a sample size of 32 companies. The study period spans from 2018 to 2023, resulting in 192 observations. In this study, dividend policy is measured using the Dividend Payout Ratio (DPR), leverage using the Debt to Equity Ratio (DER), and company size measured using Size. The results of this study indicate that leverage has a positive and significant effect on dividend policy, and company size has a negative and significant effect on dividend policy.